2021
DOI: 10.1002/j.2769-2795.2021.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota: a new player in the pathogenesis of perioperative neurocognitive disorder?

Abstract: Perioperative neurocognitive disorder (PND), including postoperative delirium and postoperative cognitive dysfunction (POCD), is a common postoperative complication in elderly patients, who represent an expanding segment of our population. PND is a multifactorial disease resulting in higher morbidity and mortality. The precise mechanism of PND is yet to be fully delineated. Identifying the modifiable risk factors and mechanisms for PND would be an important step forward in preventing such adverse events and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…The gut microbiota is a key component of the gut-brain axis. The association between disturbed gut microbiota and PND is currently a hot topic in research ( Dong et al, 2021 ). The gut microbiota is a collection of microorganisms, including bacteria, fungi, viruses, and others, living in the human gut and having a symbiotic relationship with the host, playing an important role in human health and disease development ( Chen et al, 2021 ).…”
Section: Relationship Among Peripheral Inflammation Central Nervous S...mentioning
confidence: 99%
“…The gut microbiota is a key component of the gut-brain axis. The association between disturbed gut microbiota and PND is currently a hot topic in research ( Dong et al, 2021 ). The gut microbiota is a collection of microorganisms, including bacteria, fungi, viruses, and others, living in the human gut and having a symbiotic relationship with the host, playing an important role in human health and disease development ( Chen et al, 2021 ).…”
Section: Relationship Among Peripheral Inflammation Central Nervous S...mentioning
confidence: 99%
“…A review of nine publications addressing microbiome changes with POCD incidence in animal models indicated significant changes in the microbiome in POCD mice after anaesthetic and surgery [338], with reductions in Firmicutes and increases in Proteobacteria [339]. In addition, there is evidence of the link between POCD and AD, with an increase in amyloid-β and hyperphosphorylated tau in animal models and patients with POCD [340]. One of the few human studies showed that elderly patients with POCD had reduced microbiome diversity with increased Anaerofilum (a genus common in depression) and decreased Fusicatenibacter, Coprococcus, and Dorea, among others [341].…”
Section: Post-operative Cognitive Dysfunctionmentioning
confidence: 99%
“…One of the few human studies showed that elderly patients with POCD had reduced microbiome diversity with increased Anaerofilum (a genus common in depression) and decreased Fusicatenibacter, Coprococcus, and Dorea, among others [341]. While the change in microbiome structure in POCD is due to the stress of the procedure, combined with perioperative antibiotics and opioids and restricted nutrition, it is postulated that this dysbiosis, acting on the BBB, might contribute to POCD [340].…”
Section: Post-operative Cognitive Dysfunctionmentioning
confidence: 99%